Binding Force of Non-Disclosure Agreement as Means of Trade Secret Protection in Decision No. 832/Pdt.G/2023/PN.Jkt.Brt - Evan Dori; Muthia Sakti (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
This research is entitled “Binding Force of Non-Disclosure Agreement as Means of Trade Secret Protection in Decision No. 832/Pdt.G/2023/PN.Jkt.Brt” The object of this study is the regulation and implementation of NDAs within the framework of Indonesia’s positive legal system. The purpose of this research is to explain the form of overlap between civil law and intellectual property law, which results in weak legal certainty in the protection of trade secrets. The research method applied is normative juridical research with a statutory and case study approach, focusing on Decision No. 832/Pdt.G/2023/PN.Jkt.Brt. The results show that NDAs are legally recognized as innominate agreements under Article 1338 of the Indonesian Civil Code. However, their application in the context of trade secret protection remains ineffective due to differences in legal regimes and institutional arrangements under Law No. 30 of 2000. The case analysis demonstrates that the court still interprets NDA violations narrowly as contractual breaches rather than as infringements of intellectual property rights. This condition reflects that the function of NDAs as instruments for trade secret protection has not yet been fully optimized. The findings of this research illustrate the need to strengthen the synergy between civil law and intellectual property law in the practice of trade secret protection in Indonesia.